1983
DOI: 10.1007/bf02281001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise training on aerobic fitness in children after open heart surgery

Abstract: Graded treadmill tests to maximal exercise were given to 24 children 1 year or more after open-heart surgery and to 26 age- and sex-matched controls, before and after 9 weeks of exercise training to test whether or not they could increase their aerobic fitness levels. The corrected cardiac lesions included tetralogy of Fallot, aortic stenosis, transposition of the great arteries and atrioventricular canal (AVC). Maximal exercise variables measured were heart rate (HR), oxygen consumption (VO2), and workload (s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 16 publications
1
28
0
1
Order By: Relevance
“…As was pointed out by Cumming [12], these findings probably resulted in part from a greater maximal effort during the exercise but also from a better physical fitness of the Canadian children due to a greater level of physical activity in general compared to U.S. children. The importance of physical activity is also supported by subsequent training studies after ICR, which all showed improved physical performance after training [5,7,25,74], and by observations that patients who participate in varsity sports after ICR perform better than nonathletes [36,93].…”
Section: Work Performancementioning
confidence: 91%
See 2 more Smart Citations
“…As was pointed out by Cumming [12], these findings probably resulted in part from a greater maximal effort during the exercise but also from a better physical fitness of the Canadian children due to a greater level of physical activity in general compared to U.S. children. The importance of physical activity is also supported by subsequent training studies after ICR, which all showed improved physical performance after training [5,7,25,74], and by observations that patients who participate in varsity sports after ICR perform better than nonathletes [36,93].…”
Section: Work Performancementioning
confidence: 91%
“…If training is carried out at home, true verification of the training activity is a most difficult task. Nevertheless, four such studies were reported [5,7,25,74] involving a total of 30 patients (range 1-16). Duration of training varied from 6 to 12 weeks with two or three sessions per week of variable intensity.…”
Section: Exercise Training and Serial Studiesmentioning
confidence: 94%
See 1 more Smart Citation
“…In those studies that have detected an improvement in exercise function, the mechanisms that were responsible for the observed improvements have not been elucidated. 15,[18][19][20][21][22][23][24][25] We therefore undertook this study to characterize more clearly the effect of a 12-week pediatric cardiac rehabilitation program on the exercise performance and cardiopulmonary function of children with CHD and to define the physiologic mechanisms that account for any improvements that may be observed.…”
mentioning
confidence: 99%
“…The most wide-scale studies of physical loads' influence in cardio-rehabilitation programs for persons with CHD were made by J. Rhodes [26][27][28] -increase of peak VO 2 and maximal load for long period; P. E. Longmuir [20,21] -long term improvement of physical fitness indicators; L. M. Bradley [10] -improvement of peak VO 2 and endurance; I. C. Balfour [8] -improvement of peak VO 2 ; B. Goldberg [16] -improvement of maximal power and workability, influence on peak VO 2 was absent; H. D. Ruttenberg [29], P. M. Fredriksen [13] -improvement of endurance, influence on peak VO 2 was absent.…”
mentioning
confidence: 99%